Knockdown garden chair using cam fitting fastener / Muhammad Fahmi Mohd Fuad - Mohd Fuad, Muhammad Fahmi (2019)
Knockdown system in furniture production is starting to be used globally by the well-known furniture producer. In this paper, it was focusing on the knockdown system to a garden chair. The research done is based on the design of the chair with the concept of modem furniture. This study was starts from the designing process to manufacturing process of the knockdown garden chair. The data analysis in this study was based on 130 respondents that involved in the survey. The data are interpreted in demographic analysis, descriptive analysis and comparative analysis. Demographic analysis study related to different gender, age, profession and income. The descriptive analysis of this study was to understand the knowledge of the respondent toward material, design, marketing and satisfaction. Then comparative analysis of this study was intended to compare the opinion of respondent based on gender, age, profession and income. Generally, the result indicated that the respondents agreed with all factors which the mean rate was approximately M = 4.0. Therefore, the practical of using cam fitting as a fastener for the knockdown garden chair is new approach in furniture manufacturing.